Case Report: Pulmonary sarcomatoid carcinoma complicating TP53 mutation treated successfully with Tislelizumab combined with Anlotinib—a case report - Li, Yu-Feng; Zhao, Xin-Fei; Tian, Yue; Xiao, Xin-Yao; Yan, Cai-Yun; Shen, Hua (Frontiers in Genetics, 2022)
Abstract：Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of lung malignant tumor. Conventional chemotherapy has a suboptimal effectiveness, PSC has the characteristics of rapid disease progression and poor prognosis. We herein report a 56-year-old male patient with substantial smoking history was pathologically diagnosed as PSC, cT4N0M0 IIIA stage. Peripheral blood NGS showed TP53 mutation. The patient had poor tolerance to the first-line chemotherapy regimen "albumin paclitaxel + cisplatin"，but the severe anemia was significantly improved after 5 days of antiangiogenic therapy with Anlotinib. At this time, the patient received anti-PD-1 immunotherapy with Tislelizumab. Half a month later, degree III liver injury occurred repeatedly. After excluding drug-induced liver injury, we found that HCV- RNA 3.10x10 ^ 5IU / ml and suspended all anti-tumor therapy. After the start of anti-HCV treatment with Epclusa, the treatment of Tislelizumab combined with Anlotinib was restarted, and there was no liver injury after that. The patient received monthly maintenance therapy with Tislelizumab combined with Anlotinib to the present. The pulmonary lesions continued to decrease, and only one lung cavity is left. The patient has achieved clinical complete remission(CCR) with PSF over 20 months.Our findings suggest that Tislelizumab combined with Anlotinib may be a preferred strategy in PSC complicating TP53 mutation.